Who benefits from air service agreements? The case of international air cargo operations. (September 2022) - Wu, You; Lange, Anne; Mantin, Benny
Abstract: Air service agreements between countries spell out diverse provisions, such as reciprocal capacity allocations. We analyze how such agreements, which regulate total capacity in markets, affect total welfare and its distribution. We consider the interactions between two competing cargo airlines, their end customers, logistics service providers—who serve as intermediaries between the former two agent types—as well as the policy makers. Accounting for demand uncertainty, we model this interaction as a two-stage game. In the first stage, the policy makers coordinate equal capacity allocations to the two asset providers, whereas in the second stage, the asset providers compete over prices in the spot market. Solving the model, we characterize the pricing strategies employed by the two competing capacity-constrained asset providers in the spot market when facing price sensitive demand from end customers. We further analyze the corresponding capacity decisions. We then compare this coordinated competitive setting with a collaborative setting where the two asset providers can (virtually) merge and act as a monopoly. We find that, compared with the monopoly setting, the coordinated duopoly results in lower capacity, lower profits to the asset providers, larger benefits to both end customers and logistics service providers, and overall lower total welfare. These results suggest that policy makers shall hold an open attitude towards a higher level of cooperation among the asset providers. We carry out robustness checks to verify our insights hold with three, rather than two, asset providers, with different demand distributions, when capacity is costly and when asymmetric capacities are allowed in the spot market. Highlights: We model price competition in a cargo spot market with capacity constraints. We analytically identify equilibrium prices and characterize a mixed pricing range. We explain optimal reciprocal capacity choices for the cargo market. We study welfare effects of the regulator's attempt to support a national asset provider. We find that welfare increases in collaborative settings.